The Effect of Change-Oriented Leadership and Employee Adaptability on Employee Performance, with Readiness for Change as a Mediating Variable: A Study at the Financial Education and Training Agency - Desi Restu Cahyani (International Journal Labs, 2026)
The dynamic organizational environment demands that public institutions continuously adapt and improve performance. This study aims to analyze the influence of change-oriented leadership and employee adaptability on employee performance, with readiness for change as a mediating variable in the context of organizational restructuring at the Financial Education and Training Agency (Badan Pembinaan Pegawai Keuangan or BPPK). The study uses a quantitative approach with an online survey method targeting BPPK civil servants (pegawai negeri sipil or PNS) who have worked for at least one year. A total of 146 valid questionnaires were analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS), including tests of the measurement model, structural model, and descriptive analysis. The results show that change-oriented leadership and employee adaptability have significant effects on readiness for change, and readiness for change has a significant effect on employee performance. In addition, readiness for change fully mediates the relationship between change-oriented leadership and employee performance and partially mediates the relationship between employee adaptability and employee performance. These findings confirm that improvements in employee performance during organizational change depend on the organization's ability to build employee readiness for change. Practically, the results of this research are expected to serve as the basis for BPPK policy-making in supporting adaptive and sustainable organizational restructuring.